Recent Sex Chromosome Divergence despite Ancient Dioecy in the Willow Salix viminalis. (27th April 2017) - Pucholt, Pascal; Wright, Alison E.; Conze, Lei Liu; Mank, Judith E.; Berlin, Sofia
Abstract: Sex chromosomes can evolve when recombination is halted between a pair of chromosomes, and this can lead to degeneration of the sex-limited chromosome. In the early stages of differentiation sex chromosomes are homomorphic, and even though homomorphic sex chromosomes are very common throughout animals and plants, we know little about the evolutionary forces shaping these types of sex chromosomes. We used DNA- and RNA-Seq data from females and males to explore the sex chromosomes in the female heterogametic willow, Salix viminalis, a species with ancient dioecy but with homomorphic sex chromosomes. We detected no major sex differences in read coverage in the sex determination (SD) region, indicating that the W region has not significantly degenerated. However, single nucleotide polymorphism densities in the SD region are higher in females compared with males, indicating very recent recombination suppression, followed by the accumulation of sex-specific single nucleotide polymorphisms. Interestingly, we identified two female-specific scaffolds that likely represent W-chromosome-specific sequence. We show that genes located in the SD region display a mild excess of male-biased expression in sex-specific tissue, and we use allele-specific gene expression analysis to show that this is the result of masculinization of expression on the Z chromosome rather than degeneration of female-expression on the W chromosome. Together, our results demonstrate that insertion of small DNA fragments and accumulation of sex-biased gene expression can occur before the detectable decay of the sex-limited chromosome.